Designing an Online Marketing Model for International Maritime Logistics Services with a Focus on the B2B (Business-to-Business) Approach: Identifying Barriers to Digital Adoption and Developing Strategies to Overcome Challenges in the Maritime Transport Industry - Hosseinzadeh Bakhtouri, Kamran; Bagheri, Mehdi; Jokar, Soheila (Digital Transformation and Administration Innovation, 2026)
This study aims to design an online marketing model for international maritime logistics services based on a business-to-business (B2B) approach, focusing on identifying digital adoption barriers and proposing strategic solutions to enhance marketing performance. The study employed a descriptive–analytical mixed-method design integrating both quantitative and qualitative approaches. The research population included marketing managers, digital transformation specialists, and B2B clients from international maritime logistics companies. Data collection was carried out using standardized questionnaires and semi-structured interviews. The quantitative data were analyzed through SPSS using descriptive statistics, correlation tests, and multiple regression analysis to determine the predictive relationships between digital readiness, organizational capability, technological barriers, management commitment, and online marketing performance. The qualitative data, collected through interviews with industry experts, were analyzed using NVivo software and thematic coding to identify key patterns and themes related to digital transformation, organizational behavior, and strategic innovation within maritime marketing contexts. The regression results revealed that digital readiness (β = 0.364, p < 0.001), organizational capability (β = 0.286, p < 0.01), customer trust (β = 0.195, p < 0.01), and management commitment (β = 0.244, p < 0.01) significantly and positively predicted online marketing performance, while technological barriers had a negative effect (β = -0.221, p < 0.01). The overall model explained 50.8% of the variance in marketing performance (R² = 0.508). Qualitative results identified six central themes: technological barriers, organizational barriers, customer challenges, economic and regulatory constraints, strategic enablers, and innovation opportunities. Effective online marketing in maritime logistics depends on strengthening digital readiness, organizational capability, leadership commitment, and customer trust while mitigating technological and structural barriers. The proposed model offers a strategic framework for achieving digital transformation and sustainable competitiveness in B2B maritime marketing.